1999
DOI: 10.1046/j.1365-2044.1999.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the antibacterial activity of levobupivacaine vs. bupivacaine: an in vitro study with bacteria implicated in epidural infection

Abstract: SummaryPostanaesthetic shivering affects up to 70% of patients after general anaesthesia, and may be very distressing. Various drugs have been used to treat or prevent postanaesthetic shivering, but the ideal one has not yet been found. Sixty patients undergoing elective abdominal or orthopaedic surgery under general anaesthesia were included in a randomised, double-blind study. Patients received clonidine (3 mg.kg Mean arterial blood pressure and heart rate were significantly lower in the clonidine group comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
1
26
0
2
Order By: Relevance
“…This finding has been repeated in investigations of microbial survival in other types of medication (57). Many of the candidate studies from our literature review examined the antimicrobial activity of bupivacaine at temperatures which were substantially higher than room temperature (14,33,39,(48)(49)(50)(51)(52)(53)(54). In the only study which did observe the antimicrobial activity of bupivacaine at room temperature, the local anaesthetic was found to have generally poor antimicrobial effectiveness (34).…”
Section: Effect Of Temperature On the Antibacterial Activity Of Bupivmentioning
confidence: 68%
See 1 more Smart Citation
“…This finding has been repeated in investigations of microbial survival in other types of medication (57). Many of the candidate studies from our literature review examined the antimicrobial activity of bupivacaine at temperatures which were substantially higher than room temperature (14,33,39,(48)(49)(50)(51)(52)(53)(54). In the only study which did observe the antimicrobial activity of bupivacaine at room temperature, the local anaesthetic was found to have generally poor antimicrobial effectiveness (34).…”
Section: Effect Of Temperature On the Antibacterial Activity Of Bupivmentioning
confidence: 68%
“…All have suggested that this activity is concentration-dependent (14,33,34,39,(48)(49)(50)(51)(52)(53)(54), however there is conflicting evidence as to the specifics of bupivacaine's antimicrobial activity. Some suggest that bupivacaine has good action against a variety of pathogens at clinically significant concentrations (14,50,51,54).…”
Section: Findings Of Previous Investigations Into the Antibacterial Amentioning
confidence: 99%
“…Alternativas que mereceriam melhor avaliação seriam o isômero puro S(-)-bupivacaína a 0,75%, ou a S75-R25 em maior concentração, a fim de manter a qualidade do bloqueio motor e de ampliar o grau de analgesia. A adição do isômero R(-)-bupivacaína a 25% poderia trazer benefícios teóricos, como maior potência antibacteriana contra Staphylococcus aureus, S epidermidis, Enterococcus faecalis 18 . Resta saber se a adição de 25% do R(+)-bupivacaína à formulação seria mais vantajosa quando comparada com a solução levobupivacaína a 0,75%, sendo equipotentes tanto quanto à anestesia, quanto à incidência dos efeitos tóxicos.…”
Section: Discussionunclassified
“…Alternatives deserving further evaluations would be the pure isomer 0.75% S(-) bupivacaine or S75-R25 in higher concentrations to maintain motor block quality and enhance analgesia. The association of the isomer 25% R(-) bupivacaine could have theoretical benefits, such as more antibacterial potency against Staphylococcus aureus, S. epidermidis, Enterococcus faecalis 18 . It is still to be known whether the association of 25% R(+) bupivacaine to the formulation would be more advantageous as compared to 0.75% levobupivacaine, being equipotent both in anesthesia and incidence of toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The antibacterial properties of local anesthetics and other agents used in wound infiltration are important. Previous research emphasized the antibacterial properties of bupivacaine [42][43][44] . Controversy surrounds lidocaine antibacterial properties though there are studies in the literature emphasizing its antibacterial properties 45 .…”
Section: Discussionmentioning
confidence: 99%